Compression-mode resonances in the calcium isotopes and implications for the asymmetry term in nuclear incompressibility - Howard, K.B.; Garg, U.; Itoh, M.; Akimune, H.; Bagchi, S.; Doi, T.; Fujikawa, Y.; Fujiwara, M.; Furuno, T.; Harakeh, M.N.; Hijikata, Y.; Inaba, K.; et al. (Physics letters. B, 2020)
Recent data on isoscalar giant monopole resonance (ISGMR) in the calcium isotopes 40,44,48Ca have suggested that Kτ, the asymmetry term in the nuclear incompressibility, has a positive value. A value of Kτ>0 is entirely incompatible with present theoretical frameworks and, if correct, would have far-reaching implications on our understanding of myriad nuclear and astrophysical phenomena. This paper presents results of an independent ISGMR measurement with the 40,42,44,48Ca(α,α′) reaction at Eα=386 MeV. These results conclusively discount the possibility of a positive value for Kτ, and are consistent with the previously-obtained values for this quantity.